2020
DOI: 10.1111/jpc.14821
|View full text |Cite
|
Sign up to set email alerts
|

Excessive screen time is associated with maternal rejection behaviours in pre‐school children

Abstract: AimEarly childhood screen exposure leads to multiple adverse health events and parents have a major influence on their children's screen time. Our aim was to determine the association between maternal acceptance–rejection/control behaviours and excessive screen exposure in pre‐school children.MethodsIn this cross‐sectional descriptive study, children aged 2–5 years who had daily screen time <1 h (n = 76) and >4 h (n = 62) were enrolled. A structured survey form and Parental Acceptance–Rejection/Control Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…This finding is in line with previous studies that found children's total exposure to media time was associated with physical activity of children and oral hygiene. 12,18 In our multiple regression analysis, in our study, there was a relationship between dental neglect and the age at which children were first exposed to screen time. The American Pediatric Association does not recommend exposure to the screen time for children under the age of 2, 11 while in our study it was apparent that in our cohort were exposed to screens as early as, with the majority being exposed between 12-24 and 24-36 months.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This finding is in line with previous studies that found children's total exposure to media time was associated with physical activity of children and oral hygiene. 12,18 In our multiple regression analysis, in our study, there was a relationship between dental neglect and the age at which children were first exposed to screen time. The American Pediatric Association does not recommend exposure to the screen time for children under the age of 2, 11 while in our study it was apparent that in our cohort were exposed to screens as early as, with the majority being exposed between 12-24 and 24-36 months.…”
Section: Discussionmentioning
confidence: 54%
“…12,23 Parents cited the need to occupy children while they performed housework as a common reason for permitting screen time has been demonstrated previously. 12 The study has some limitations. This study contained a small sample size, and relied on parental self-reported data only.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In our study, there was an association between abnormal scores and early first screen contact age in children with SLD; prosocial behavior problems increased as the age of the first screen contact decreased. In the study by Erat Nergiz et al (2020), mothers' low acceptance of their children and high neglect score were associated with excessive screen exposure. In another study, higher permissive and overprotective parenting style scores were associated with an increased risk of excessive screen time (Çaylan et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…These contradictory findings, which have led to current debates, may be due to several reasons. First, previous researchers have tried to speculate on the associations between digital technology use and interpersonal relationships mainly from the perspective of screen time; that is, the amount of time spent using technology [ 12 , 15 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, many researchers have recently argued that when exploring the effect of the use of digital technology, researchers should not focus on screen time, as it is no longer a valid construct (rather than the time, content may be more important) [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%